1998
DOI: 10.1016/s0896-6273(00)80630-3
|View full text |Cite
|
Sign up to set email alerts
|

CPEB-Mediated Cytoplasmic Polyadenylation and the Regulation of Experience-Dependent Translation of α-CaMKII mRNA at Synapses

Abstract: Long-term changes in synaptic efficacy may require the regulated translation of dendritic mRNAs. While the basis of such regulation is unknown, it seemed possible that some features of translational control in development could be recapitulated in neurons. Polyadenylation-induced translation of oocyte mRNAs requires the cis-acting CPE sequence and the CPE-binding protein CPEB. CPEB is also present in the dendritic layers of the hippocampus, at synapses in cultured neurons, and in postsynaptic densities of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
384
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(407 citation statements)
references
References 58 publications
10
384
2
Order By: Relevance
“…[40][41][42] Subsequently, enhanced accumulation in levels of specific mRNAs like CaMKII in dendritic spines following neuronal activity and increase in the polyadenylation and translation of stored, partially deadenylated CaMKII mRNA in mammalian synaptosomal preparations, following glutamate stimulation were observed. [43][44][45] Further studies in Aplysia, [46][47][48] Drosophila 49 and mammalian systems 50,51 showed that protein synthesis at synapses was induced by synaptic activity and provided evidence consistent with it being is required for long-term synaptic plasticity.…”
Section: Rna Regulation Is Central To Long-term Memory Formationmentioning
confidence: 97%
See 2 more Smart Citations
“…[40][41][42] Subsequently, enhanced accumulation in levels of specific mRNAs like CaMKII in dendritic spines following neuronal activity and increase in the polyadenylation and translation of stored, partially deadenylated CaMKII mRNA in mammalian synaptosomal preparations, following glutamate stimulation were observed. [43][44][45] Further studies in Aplysia, [46][47][48] Drosophila 49 and mammalian systems 50,51 showed that protein synthesis at synapses was induced by synaptic activity and provided evidence consistent with it being is required for long-term synaptic plasticity.…”
Section: Rna Regulation Is Central To Long-term Memory Formationmentioning
confidence: 97%
“…72,73 The most studied, canonical mechanism of translational activation involves the Cytoplasmic Polyadenylation Element Binding (CPEB1) protein and its regulation of CaMKII mRNA. 43,44,74,75 Activity induced translational regulation has been extensively studied in the case of CaMKII mRNA which is one of the most abundant protein in neurons especially enriched in the post synaptic density (PSD). NMDA receptor activation mediated Ca 2C entry leads to phosphorylation of the T286 residue of the pseudosubstrate domain of the a subunit (T287 of b) leading to a Ca 2C independent autonomous state of activity by autophosphorylation.…”
Section: Rna Regulation Is Central To Long-term Memory Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Four CPEB isoforms are found in the mouse (Theis et al, 2003). One of which, CPEB-1, has been detected at postsynaptic sites of hippocampal neurons and participates in local NMDAR-dependent polyadenylation of αCamKII and other dendritic mRNAs (Huang et al, 2003;Huang et al, 2002;Wells et al, 2001;Wu et al, 1998). Experiments in CPEB-1 deficient mice revealed that synaptic capture of L-LTP was partially affected in those mice (Alarcon et al, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…12 This mechanism has also been shown to control poly(A) tail length in mammalian cells. 13,14 Cytoplasmic polyadenylation is mediated by cytoplasmic polyadenylation binding protein (CPEB), which binds to the highly conserved cytoplasmic polyadenylation element (CPE) in the 3 0 UTR of mRNA. 15 Here, we show that CPEB1 and CPEB2 play a role in the translational control of TWIST1 in a CPE-dependent manner.…”
Section: Introductionmentioning
confidence: 99%